О традициях Ф. М. Достоевского в творчестве У. Фолкнера - Романов, Юрий Александрович (Петрозаводский государственный университет, 2015)
Рассматриваются традиции творчества Достоевского, оказавшие влияние на художественный мир Фолкнера и его мировоззрение: стремление к познанию широты человеческой нравственной природы, постановка человека в крайние, исключительные обстоятельства, изображение его в состоянии нравственного поиска, напряженной внутренней борьбы с самим собой, всепроникающий психологизм с использованием потока сознания при передаче духовной жизни персонажей. Прослеживаются биографические параллели Достоевского и Фолкнера, делается вывод о сопоставимости морально-нравственных идеалов русского и американского классиков.

The article focuses on the traditions of Dostoevsky's works, which influenced both W. Faulkner ‘s worldview and his artistic world: a desire to explore the depth of the human moral nature by placing a man into extreme and exceptional circumstances; description of a man in a state of moral search, intense internal struggle with himself; employment of pervasive psychology based on the “stream of consciousness” reflecting the process of characters’ spiritual life transition. Biographical parallels in the lives of Dostoevsky and Faulkner are identified. Conclusions on the comparability of moral ideals of the Russian and American classics are made.
On F. M. Dostoevsky’s traditions in W. Faulkner’s works
Keywords: Достоевский Федор Михайлович; Фолкнер Уильям; писательское мастерство; поток сознания; биографические параллели; морально-нравственный идеал; Dostoevsky; Faulkner; comparative studies; literary tradition; craftsmanship of the writer; stream of consciousness; biographical parallels; moral and ethical ideal